Igniting active engagement in pre-service teachers in STEM education: A comprehensive systematic literature review - Kamarrudin, Haryati; Talib, Othman; Kamarudin, Nurzatulshima; Ismail, Normala (Secholian Publication, 2023)
Active engagement is a topic of research in instructional approaches within education.Research reveals that numerous benefits appear once students seem to be active and gain higher-order thinking skills, increase motivation and are engaged in their learning. Although there are numerous studies on active engagement in Science, Technology, Engineering and Mathematics (STEM) education, the effort to conduct a systematic review of this area of research has been complex due to the lack of review procedures, which presents a significant dispute for authors to clarify. Thus, a systematic literature review regarding active engagement in STEM education will be conducted in this research. Five key methodological steps led the review: research questions formulation, systematic search strategies depending, critical quality appraisal, as well as data extraction and analysis. Relying on the thematic analysis, four major themes were revealed: (1) critical thinking, (2) collaboration, (3) interaction, as well as (4) encouragement. Findings from the four themes further entail four relevant activities: lectorials, exploration, sharing knowledge, and assessment. According to the findings of the papers reviewed, getting pre-service teachers involved in active engagement activities leads to more comprehensive benefits on pre-service teachers' attitudes, problem-solving skills, and achievement in learning activities.